PERBANDINGAN PENGATURAN TINDAK PIDANA ABORSI MENURUT HUKUM POSITIF INDONESIA DAN HUKUM ISLAM - R. Dyah Siti Safira; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
A woman becomes pregnant unwanted and she cannot accept the situation as her fate, so she does all sorts of effort to abort her womb. The formulation of the problem, how to compare the arrangement of abortion based on Positive Law in Indonesia and according to Islamic Law. What is the ideal of abortion crime of rape victims so far according to Positive Law in Indonesia and Islamic Law.The purpose of this research is to know the setting of abortion crime according to Positive Law in Indonesia and Islamic Law to know comparison of abortion based on Positive Law in Indonesia and Islamic Law. This type of research is normative research which discusses legal principles, legal system, legal synchronization level, legal history and comparative law of problem based on the prevailing laws and regulations by prioritizing library materials and its implementation in practice. Research conducted by the author is an analytical descriptive research.Conclusion Comparison of arrangement of abortion crime according to Positive Law in Indonesia and according to Islamic Law is seen from positive criminal law of abortion is categorized as a crime refers to Law Number 36 Year 2009 on Health, Criminal Code (Penal Code), and Government Regulation on Reproductive Health. The Criminal Code explicitly states the abortion of violations of law and criminal acts under Article 346 of the Criminal Code and there is no exception, the Health Law Article 75, the aspect of Islamic law of abortion in the Qur'an in Sura An-Nisa 'verse 93, Surat al-Isra 'verse 31, Hadith Muttafaq'alaih, and Ijma' ie MUI Fatwa Number 4 Year 2005 regulates the abortion. In Islamic law illegitimate abortion lawya because like killing humans and sanctions got a very big sin from Allah SWT except that not yet 40 days and for medical reasons. Ideally, the abortion of rape crime victims according to Positive Law in Indonesia and Islamic Law that the Positive Law of Indonesia provides legal protection against the act of abortion provocatus on rape victims with some requirements as medical reasons such as Article 75 paragraph (3), 76 Law Number 36 Year 2009. Revision of Law Number 36 Year 2009 on Health abortion is allowed not only limited medical reasons to save the life of the mother of emergency, but also pregnancy due to rape and incest, pregnant women suffering from severe mental disorders, and the fetus has severe congenital defects. Islamic law does not permit abortion, but seeing the psychological effects that rape women suffer so much, the considerations based on the rules of fikiyah, abortion due to rape may be justified by reason and abortion notes of indications of medical emergency and pregnancy due to rape, abortion may be performed before the age of 40 day is calculated from the last experience of menstruation.Keywords: Abortion-Positive Law in Indonesia-Islamic Law